The Economic Effects of Providing Legal Status to DREAMers - Francesc Ortega; Ryan Edwards; Amy Hsin (Institute of Labor Economics (IZA), 2018)
This study quantifies the economic effects of two major immigration reforms aimed at legalizing undocumented individuals that entered the United States as children and completed high school: Deferred Action for Childhood Arrivals (DACA) and the DREAM Act. The former offers only temporary legal status to eligible individuals; the latter provides a track to legal permanent residence. Our analysis is based on a general-equilibrium model that allows for shifts in participation between work, college and non-employment. The model is calibrated to account for productivity differences across workers of different skills and documentation status, and a rich pattern of complementarities across different types of workers. We estimate DACA increased GDP by almost 0.02% (about 3.5 billion), or 7,454 per legalized worker. Passing the DREAM Act would increase GDP by around 0.08% (or 15.2 billion), which amounts to an average of 15,371 for each legalized worker. The larger effects of the DREAM Act stem from the expected larger take-up and the increased incentive to attend college among DREAMers with a high school degree. We also find substantial wage increases for individuals obtaining legal status, particularly for individuals that increase their educational attainment. Because of the small size of the DREAMer population, legalization entails negligible effects on the wages of US-born workers.
Keywords: D7; F22; H52; H75; J61; I22; I24; 330; immigration; DREAMers; legalization; undocumented